2017
DOI: 10.1002/14651858.cd007529.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and umbilical Doppler ultrasound in high-risk pregnancies

Abstract: Background-Abnormal blood flow patterns in fetal circulation detected by Doppler ultrasound may indicate poor fetal prognosis. It is also possible false positive Doppler ultrasound findings could encourage inappropriate early delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 71 publications
2
147
3
9
Order By: Relevance
“…This same pattern was observed in the present study, where SGA pregnancies had an increased risk of stillbirth from 33 weeks onwards. Pilliod et al [3] demonstrated a dose-response effect, where SGA babies below the 3rd centile were at greater risk of stillbirth across all gestations compared with AGA LGA v. AGA*, RR of stillbirth (95% CI) 28 -…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This same pattern was observed in the present study, where SGA pregnancies had an increased risk of stillbirth from 33 weeks onwards. Pilliod et al [3] demonstrated a dose-response effect, where SGA babies below the 3rd centile were at greater risk of stillbirth across all gestations compared with AGA LGA v. AGA*, RR of stillbirth (95% CI) 28 -…”
Section: Discussionmentioning
confidence: 99%
“…[27] This method can increase the ability to detect fetuses with pathological growth restriction and reduce perinatal mortality in high-risk women. [28] Doppler velocimetry conducted at earlier gestations has poor predictive value in detecting late-onset placental insufficiency. [29] In SA, significant challenges persist with Doppler measurement, as a large number of perinatal deaths occur in healthy mothers who are clinically considered low risk [13] and are therefore not referred for Doppler screening.…”
Section: Researchmentioning
confidence: 97%
“…induction of labor). Indeed, antenatal detection of high‐risk fetuses is associated with a significant reduction in stillbirth and perinatal morbidity rates.…”
Section: Introductionmentioning
confidence: 99%
“…In fetal growth restriction (FGR), Doppler ultrasound examination can be used to distinguish between fetuses that are at risk of adverse perinatal outcome and those that are constitutionally small. Current FGR guidelines recommend umbilical artery (UA) Doppler as an important surveillance tool, since its clinical effectiveness in high‐risk pregnancies has been reported in a Cochrane review of 18 randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%